Solid-state reaction synthesized Pd-doped tin oxide thick film sensor for detection of H2, CO, LPG and CH4 - Choudhary M.; Mishra V.N.; Dwivedi R. (My University, 2025)
This paper deals with the synthesis of tin oxide (SnO2) nano-powders by a solid-state reaction technique. The synthesized powders have been characterized by simultaneous thermo gravimetric and differential thermal analysis (TG-DTA) and X-ray diffraction (XRD) techniques. Suitable calcination temperature is established by XRD and TG-DTA analysis. Thick film sensors have been developed from as-prepared undoped and palladium (Pd) doped (0.5 and 1 wt%) SnO2 powders using screen printing technology for the detection of various pollutant gases such as, hydrogen (H2), carbon monoxide (CO), liquefied petroleum gas (LPG) and methane (CH4). The surface of the thick film sensor has been characterized by field emission scanning electron microscopy (FESEM). The sensing characteristics of thick films have been studied from the aspect of crystallite size of sensing material and microstructure of the thick film surface. It is found that SnO2 doped with 1 % Pd exhibits the maximum sensitivity (79 %) towards CO gas along with fast response/recovery time (80 s, 197 s) and almost insensitive for H2, LPG and CH4. © 2013 Springer Science+Business Media New York.